Exploring praxia deficits in bipolar disorder: A cross-sectional analysis of functionality and quality of life: Praxia in bipolar disorder - Özönder Ünal, İpek (Journal of Surgery and Medicine, 2023)
Background/Aim: Patients with bipolar disorder often experience praxia deficits, which might impede their functionality and quality of life. This study sought to delve into praxis defects in these patients, contrasting their praxia performance with healthy controls and illuminating the interrelation between praxia performance, functionality, and quality of life. Methods: In this cross-sectional study conducted from February to July 2023, we enrolled 203 patients diagnosed with bipolar disorder 1. Participants were recruited from the Ibni Sina and Sifa Community Mental Health Centers, both of which are affiliated with the Istanbul Tuzla State Hospital. Additionally, 201 healthy controls (HC) were recruited, primarily from the friends and relatives of the hospital staff. Patients diagnosed with bipolar disorder 1, between 18 and 65 years of age, were included based on their diagnosis as determined by the Structured Clinical Interview for DSM-5 Clinical Version (SCID-5-CV). Their right-handedness was ascertained via the Edinburgh Handedness Inventory. To minimize the confounding effects of acute mood episodes on praxia deficits, patients were required to score below 5 on the Young Mania Rating Scale (YMRS) and 7 or lower on the 17-item Hamilton Depression Rating Scale (HDRS). This criterion ensured the exclusion of individuals experiencing an active mood episode. Additionally, participants needed to have been in remission for at least six months. Healthy controls, aged 18-65 and confirmed as right-handed, were included, provided they had no personal or familial history of psychiatric conditions. A detailed interview using SCID-5-CV confirmed that the healthy controls had no history or suspicion of bipolar disorder (BD) or any other psychiatric disorder and no relatives with a psychiatric disorder. All participants (203 bipolar disorder patients and 201 healthy controls) underwent evaluations using the Test for Upper Limb Apraxia (TULIA), while the bipolar cohort received the Global Functioning Assessment-Functioning (GAF-F) and the World Health Organization Quality of Life-Brief Version (WHOQOL-BREF). Statistical analyses were conducted using SPSS 22.0. Results: We identified a critical TULIA score threshold of 217, which differentiates bipolar patients from healthy individuals with a sensitivity of 79.3% and a specificity of 77.1% (area under the curve (AUC) 0.799, P<0.001). TULIA scores in bipolar patients were significantly positively correlated with functionality (GAF-F; r=0.502, P<0.001) and quality of life-general health (WHOQOL; r=0.389, P<0.001). TULIA pantomime subscores (OR=0.92, 95% CI 0.86-0.99, P=0.022) and CPZ use of more than 250mg per day (OR=2.24, 95% CI 1.19-4.21, P=0.012) were independent predictors of impairment in functioning in bipolar patients. Conclusion: Praxia deficits in bipolar disorder patients may be intricately tied to specific clinical features that influence both their functionality and life quality. Comprehensive praxia deficit assessments can pave the way for devising tailored interventions, enhancing praxia and, by extension, the quality of life of bipolar patients.